EFEKTIVITAS PEMBELAJARAN BERBASIS STEAM TERHADAP KEMAMPUAN BERPIKIR KRITIS (HOTS) ANAK USIA 5-6 TAHUN - Ardhana Reswari (Universitas Islam Lamongan, 2021)
This study aims to determine the effectiveness of STEAM based learning on critical thinking skills (HOTS) in children aged 5-6 years at kindergarten District Ngajum Malang Regency. This research is categorized as quantitative research which is using Quasi Experimental research design Nonequivalent Control Group Design. The research was conducted in group B at RA Diponegoro and TK Bhayangkari. The research data are collected using observation and documentation technique. Data were analyzed using statistical analysis by Anova with SPSS 21.0 for Windows. This research results show that: (1) Â is 361,182 with significant value 0.000 < 0.05, so the hypothesis of STEAM based learning on critical thinking skills (HOTS) in children can be accepted. According this research result, it can be concluded that the effectiveness of STEAM based learning that effect of to critical thinking skills (HOTS) in children aged 5-6 years.